Lansia Anggota Kelompok Bina Keluarga Lansia (BKL) Adalah Sebuah Aset (Potensi) Bagi Pembangunan Di Masyarakat Rw 04 Pancoran, Jakarta Selatan - Yanto, Juli; Bantarti, Wisni (Jurnal Ilmu Kesejahteraan Sosial, 2016)
This research depict a new paradigm of elderly. All this time, the elderly have been thouht as an unproductive age group, dependent to the family, consumptive, used up of the health budget, and useless jugment in the community. However, the existing of the BKL IMPALA group in the community indicates that the elderly in the BKL IMPALA group as an asset or potential human resources to participate in the development of RW 04 Pancoran, and they are not family’s or development’s burden. The result of this research that the elderly have been health, and active in every BKL IMPALA’s or community’s activity. Their activities have been shown in every activity that held by BKL IMPALA and they are to become motivator in every activity. They always give an very good idea to the RW 04 development. For BKL IMPALA group, it is better to keep giving opportunity to the elderly to be active in the all activities in the community. For further research can be done by focusing on how the elderly that are an asset for the development can generate the good values or wisdoms to the youth as an further generation in RW 04 Pancoran, South Jakarta.